2016
DOI: 10.6024/jmbai.2016.58.1.1875-01
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and culture of the marine rotifer Colurella adriatica Ehrenberg, 1831 (Family: Lepadellidae) from Andaman & Nicobar Islands: A promising live feed for larval rearing of high value shellfishes and finfishes

Abstract: An extremely small rotifer was isolated from the micro zooplankton samples collected during February, 2014 from Havelock islands of Andaman and Nicobar Islands. The species was identified as Colurella adriatica Ehrenberg, 1831 (Family: Lapadellidae). Its lorica length under culture period ranged from 47.530 to 98.868 µm and width from 34.308 to 56.277 µm. The size of the eggs, neonates and adults are also documented. Comparison of size of C. adriatica with Brachionus plicatilis (L type) and B. rotundiformis (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We know that lighting is an important aspect of housing protocols and not having consistent information can have an impact on replicating a study. We also found it noteworthy to include that out of the 21 studies, only two brought up the use of an artificial moonphase (Fobert et al ., 2021; Madhu & Madhu, 2007). The only variable out of the water parameters that seemed to vary more than expected was salinity, which was due to some of the studies deliberately using estuarine or brackish water as the main water source for the system to see if anemonefish could be raised in such waters.…”
Section: Resultsmentioning
confidence: 99%
“…We know that lighting is an important aspect of housing protocols and not having consistent information can have an impact on replicating a study. We also found it noteworthy to include that out of the 21 studies, only two brought up the use of an artificial moonphase (Fobert et al ., 2021; Madhu & Madhu, 2007). The only variable out of the water parameters that seemed to vary more than expected was salinity, which was due to some of the studies deliberately using estuarine or brackish water as the main water source for the system to see if anemonefish could be raised in such waters.…”
Section: Resultsmentioning
confidence: 99%
“…It's found that the visual census method was effectively employed for the reef fish diversity documentation from the various parts of the country. From Lakshadweep Pillai 2002, 2005), the Andaman and Nicobar Islands (Madhu and Madhu 2007;Rajaram and Nedumaran, 2009) and from islands off the central western coast states of Goa and Karnataka (Sluka and Lazarus 2004, 2006Zacharia et al 2008;Thomas et al 2011). Another version of UVC, the rapid surveys have an immense role in the ichthyofaunal diversity study especially in an ecosystem like rocky reefs which deserve a more conservative approach for biodiversity assessment (Rajan et al 2021).…”
Section: Discussionmentioning
confidence: 99%